Shariah Mobile Banking Adoption Trends: Analysis Mob Mentality, Reputation, Perceived Risk, and Islamic Financial Literacy - Fitri Fadilah Widyaputri; Edy Yusuf Agung Gunanto (Universitas Airlangga, 2023)
ABSTRACTThis study aimed to analyze the factors that influence customer decisions in using Islamic mobile banking services. In this study, a total of 200 respondents were collected through purposive sampling technique with the criteria of having used or currently using mobile banking services from Islamic banks in Semarang City, respondents answered online surveys through google forms as primary data collection. The methodology in this study was using PLS-SEM. The study findings show that the factors of mob mentality, reputation, perceived risk, and Islamic financial literacy have a positive and significant influence on the decision to use Islamic mobile banking. The four factors have a total influence of 87% on the decision to use Islamic mobile banking services. This finding implies that these factors need to be considered by customers and banks. Islamic banking must continue to strive for a level of security, data confidentiality and customer trust in a more creative, convenient, and effective mobile banking features and services system so that customers still feel their decision to use Islamic mobile banking services is right.Keywords: Mob Mentality, Reputation, Perceived Risk, Islamic Financial Literacy. ABSTRAKStudi ini memiliki tujuan untuk menganalisis faktor-faktor yang berpengaruh terhadap keputusan nasabah dalam menggunakan layanan mobile banking syariah. Pada studi ini, dikumpulkan sejumlah 200 responden melalui teknik purposive sampling dengan kriteria pernah atau sedang menggunakan layanan mobile banking dari bank syariah di Kota Semarang, responden menjawab survei secara online melalui google forms sebagai pengumpulan data primer. Metodologi pada penelitian ini yaitu menggunakan PLS-SEM. Hasilnya menunjukkan bahwa faktor-faktor mentalitas gerombolan, reputasi, persepsi akan resiko, dan literasi keuangan syariah memiliki pengaruh positif dan signifikan terhadap keputusan penggunaan mobile banking syariah. Keempat faktor tersebut memiliki total pengaruh sebesar 87% terhadap keputusan penggunaan layanan mobile banking syariah. Penemuan ini memberikan implikasi bahwa faktor-faktor tersebut perlu dipertimbangkan oleh nasabah dan pihak perbankan. Perbankan syariah harus tetap mengupayakan tingkat keamanan, kerahasiaan data dan kepercayaan nasabah dalam sistem fitur dan layanan mobile banking yang lebih kreatif, nyaman, serta efektif agar nasabah tetap merasa keputusannya menggunakan layanan mobile banking syariah adalah tepat.Kata Kunci: Mob Mentality, Reputation, Perceived Risk, Islamic Financial Literacy.